Pemikiran Ekonomi Ilmuwan Muslim Kontemporer - Uswatun Khasanah; Hilda Safitri; Muhammad Farhan Ahnaf; Hilmi Dzaki; Muhammad Taufiq Abadi; Muhammad Aris Syafi’i (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The economic thinking of contemporary Muslim scholars covers various aspects, such as the Islamic financial system, zakat, waqf, and trade based on Islamic principles. The purpose of writing this article is to describe the Economic Thought of Contemporary Muslim Scholars from the Figures Ahmad Adzhar Basyir, K.H. Sahal Mahfud, K.H. Abdullah bin Nuh, Muhammad Amin Azis. This writing method uses a literature review approach sourced from various articles, journals, and books relevant to the research topic. Many challenges and opportunities faced by contemporary Islamic economic thinkers in disseminating their thoughts in a diverse global society. Contemporary Islamic economic thought has an important value in creating a more just and sustainable economic system based on Islamic principles. Their efforts in integrating religious values with economic science can provide valuable insights for the development of an inclusive and sustainable global economy.